1993
DOI: 10.1136/hrt.70.6.524
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid and risk of sudden cardiac death.

Abstract: The percentage content of linoleic acid in adipose tissue was inversely related to the risk of sudden cardiac death. Populations with a high risk of sudden cardiac death may benefit from increasing their dietary intake of polyunsaturated fatty acid oils, principally from cereals and vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 14 publications
(3 reference statements)
2
9
0
Order By: Relevance
“…16 These findings are in agreement with experimental evidence in animals that omega-3 fatty acids reduce the vulnerability of the ischemic myocardium to ventricular fibrillation. 44 -46 Our patients were admitted to coronary care units.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…16 These findings are in agreement with experimental evidence in animals that omega-3 fatty acids reduce the vulnerability of the ischemic myocardium to ventricular fibrillation. 44 -46 Our patients were admitted to coronary care units.…”
Section: Discussionsupporting
confidence: 86%
“…[7][8][9][10][11][12] Similarly, studies of the association of plasma or tissue levels of fish oils and incidence of myocardial infarction have yielded conflicting results. [13][14][15][16][17] A randomized trial of diet in patients after myocardial infarction found a significant reduction in mortality caused by ischemic heart disease in the group assigned to consuming fatty fish 2 to 3 times per week, but the number of ischemic events was not reduced. 18 ALA may also reduce platelet aggregability, 19 -21 either by modulating the effect of arachidonic acid, 22,23 or through desaturation and elongation to EPA.…”
mentioning
confidence: 99%
“…The most striking change on the walnut diet was the increase in linoleic acid in all plasma fatty acid fractions and the increase in alpha linolenic acid in plasma triacylglycerol. There is reasonably convincing evidence that linoleic acid may be protective against CHD (Riemersma et al, 1986;Hetzel et al, 1989;Roberts et al, 1993) and there is emerging evidence of the importance of dietary alpha linolenic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Those in vestigations revealed that a highly saturated fatty acid concentration in fat tissue is corre 124 C'han/Tsai/Chiang/Hong Trilinolein and Coronary Ligation lated with a high incidence rate of ventricular arrhythmia in patients with acute myocardial infarction [27], Also an inverse relation oc curs between linoleic acid and the risk of angi na and of sudden cardiac death [28,29], In animal studies, mortality and severity of ar rhythmia following coronary ligation were found to be reduced in animals fed with a linoleic acid-rich diet [7,8,30]. Results here are compatible with those reports which claimed a beneficial effect from such a diet.…”
Section: Discussionmentioning
confidence: 99%